PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF EDUCAPLAY TERHADAP HASIL BELAJAR IPAS MATERI AKU DAN KEBUTUHANKU SISWA KELAS IV SD NEGERI PERTIWI LAMGAROT ACEH BESAR - Hasmawati; Mislinawati; Suci Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low learning outcomes of students in IPAS learning are caused by the lack of innovative media utilization, which makes students less enthusiastic and tends to be passive in learning, resulting in only 18 out of 39 students achieving the learning objective attainment criteria of 75. This condition encouraged the researcher to implement Educaplay interactive learning media as a more attractive alternative solution. This study aims to describe the implementation of Educaplay interactive learning media on IPAS learning outcomes of the material "Aku dan Kebutuhanku" for fourth grade students of SD Negeri Pertiwi Lamgarot Aceh Besar. This study uses a descriptive qualitative approach with 39 students as subjects, data collection instruments in the form of teacher and student activity observation sheets and a written test of 20 multiple choice questions. The data analysis technique uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of Educaplay was carried out very well, as evidenced by the results of teacher and student activity observations which showed high involvement and enthusiasm in the very good category throughout the learning process. Student learning outcomes showed an average score of 85.12 with classical completeness reaching 87% where 34 out of 39 students were declared to have passed, so it can be concluded that the implementation of Educaplay interactive learning media is able to create an active, interactive, enjoyable learning atmosphere and has a positive impact on student learning outcomes in IPAS learning in elementary school